Elastostatic analysis of single core shear walls subjected to lateral loadings using isoparametric finite element method - Botuyan, Allan Espanola
An elastostatic finite element analysis of single core shear walls using flat shell element is presented. The flat shell element is a combination of a membrane plane stress element and a plate bending element. The analysis being three dimensional considers the out-of-plane deformation if the flat shell element (i.e the out-of-plane displacement of the slab connected to the core shear wall.) A numerical method is implemented in a computer program called Shell Element Analysis Systems (SEAS). Several illustrative models, representing slab core wall structural combinations, are presented. These include combinations of slabs, walls, and columns acted upon by static lateral loads.